ENTREPRENEURIAL INTENTIONS OF STUDENTS OF HIGHER EDUCATION SCHOOLS IN THE TERRITORY OF AUTONOMUS PROVINCE OF VOJVODINA - Jovin, Slobodanka; Jošanov Vrgović, Ivana (International Journal of Economic Practice and Policy, 2019)
Entrepreneurship is the most important development potential of a modern economy. Students and their entrepreneurial intentions encourage the creation of an entrepreneurial society, employment growth and innovation. In order to stimulate innovation, it is necessary to improve the quality of cooperation between the economy and scientific research institutions in which young people's entrepreneurship and their innovation play an important role. In this paper, 442 students of higher vocational schools from the territory of AP Vojvodina were empirically examined. The results pointed to the existence of the desire and intention of students to start and run their work, and that most students want to open their company in the future. The results also showed that students believe that the planned time between completing studies and setting up their own work is from 3 to 5 years.
Keywords: education||; ||obrazovanje; vocational schools||; ||visoke strukovne škole; students||; ||studenti; intention||; ||namera; innovation||; ||inovacija; entrepreneurial intentions||; ||preduzetničke namere; entrepreneurship||; ||preduzetništvo